The Relationship between Perceived Empowerment Levels of Employees in Turkey - SELÇUK ARPINAR, MELİKE (My University, 2020)
Abstract: The main purpose of this study which concentrates on the common context of empowerment levels and determines the content is to find out the relationship between levels of perceived empowerment. Besides, the subgoal of this article is to define the differences for the empowerment levels according to some demographic distinctive of the participants. The research has been obtained from 203 people working in foreign trade organizations placed in Istanbul. A scale was used to define the personnel empowerment levels with a question form for demographic characteristics. The data were analyzed by Mann Whitney-U and Kruskal Wallis tests. As a result of the research; there are positive relationships between some levels, but in others there are not. In addition to this, as a subgoal of the study, it has reached the result that the perceived levels of empowerment did not differ according to gender and education variables however they indicate differences according to age, experience, number of organizations worked, department and position. Keywords: Employee Empowerment, Empowerment Levels, Foreign Trade Companies
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Sosyal Psikoloji; Endüstri ve Örgüt Psikolojisi; İşletme; Yönetim ve Organizasyon; İnsan Kaynakları Yönetimi; Social Sciences and Humanities; Psychology; Social Psychology; Industry and Organizational Psychology; Management; Management and Organization; Human Resources Management; Temel Bilimler (SCI); Sosyal Bilimler (SOC); Ekonomi ve İş; PSİKOLOJİ, SOSYAL; İŞLETME; YÖNETİM; Natural Sciences (SCI); Social Sciences (SOC); PSYCHOLOGY; ECONOMICS & BUSINESS; PSYCHOLOGY, SOCIAL; BUSINESS; MANAGEMENT; Genel Karar Bilimleri; Karar Bilimleri (çeşitli); Strateji ve Yönetim; Genel Psikoloji; Genel İşletme, Yönetim ve Muhasebe; İşletme ve Uluslararası Yönetim; Psikoloji (çeşitli); Pazarlama; Sosyal Bilimler ve Beşeri Bilimler; General Decision Sciences; Decision Sciences (miscellaneous); Strategy and Management; General Psychology; General Business, Management and Accounting; Business and International Management; Psychology (miscellaneous); Marketing; Social Sciences & Humanities